Balanced strength-toughness, thermal conductivity and self-cleaning properties of PMMA composites enabled by terpolymer grafted carbon nanotube. (19th February 2021) - Song, Shiqiang; Li, Qinglan; Zhang, Cuifen; Liu, Zijin; Fan, Xin; Zhang, Yong
Abstract: Achieving a balanced strength-toughness in polymer composites is a challenge largely because of poor interfacial interaction between the fillers and matrix. Here, we report that terpolymer grafted multi-wall carbon nanotubes (Ter-CNT) imparted good dispersion of CNT in matrix and strong CNT-matrix interaction. With the addition of 2 vol% filler into polymethyl methacrylate (PMMA) matrix, the composite exhibited simultaneously a balanced strength-toughness property with flexural strength of 72.3 MPa, toughness of 10.1 MJ m −3, which increased by 40.1% and 578% compared with those of pure PMMA. In addition, the composite also shows a high static contact angle (110.3°), and thermal conductivity (0.50 Wm K −1 ), which endow the composite with good self-cleaning and thermal management capabilities. Thus, this preparation process shows guidance for the design of polymer composite with integrated high strength-toughness, thermal conductivity and good self-cleaning.